Literasi Anti Hoaks dan Sosialisasi Pelaksanaan Pemilu 2024 pada Generasi Z melalui Webinar - Melati Mediana Tobing (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
The fierce competition between political parties and legislative candidates tends to use various methods to win the 2024 elections, including using fake news or hoaxes. Generation Z, who have no experience in conducting general elections, are trapped in a spiral of information on various social media platforms, making it difficult to make their choices and leading to irrational voters and